THE IMPACT OF LEADERSHIP ON ESPRIT DE CORPS IN ENHANCING SERVICE QUALITY AT BHAYANGKARA SARTIKA ASIH HOSPITAL BANDUNG - Novi Anggraini Siregar; Vip Paramarta; Etty Sofia Mariati Asnar (Jurnal Manajemen Kesehatan Indonesia, 2026)
Bhayangkara Sartika Asih Hospital Bandung experienced a decline in the Public Satisfaction Index based on a survey conducted from July to September 2024, indicating potential problems in hospital services, particularly in terms of service quality and patient satisfaction. This study aims to analyze the effect of leadership on esprit de corps and its impact on service quality at Bhayangkara Sartika Asih Hospital Bandung. The research employed a quantitative approach using survey data collected from 124 respondents across various hospital divisions. The data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. The findings revealed that effective leadership has a significant positive impact on esprit de corps, which in turn positively affects service quality. The sense of camaraderie built through good leadership strengthens collaboration among employees, increases motivation, and enhances performance in delivering better patient care. The study also found that leadership directly contributes to service quality, while esprit de corps plays a mediating role in this relationship. This study contributes to the literature by empirically demonstrating the mediating role of esprit de corps in the relationship between leadership and service quality in a healthcare setting. Based on these findings, it is recommended that the hospital strengthen leadership training, enhance employee empowerment, and implement regular evaluations to improve service quality.Keywords:  leadership, esprit de corps, service quality, healthcare, PLS-SEM